Kinerja Aparatur Sipil Negara Dalam Pembinaan Anak Jalanan Pada Dinas Sosial Kota Kendari - Farita, Uul Nur; Batara, Suriyani Bunga; Darpin, Darpin (Universitas Halu Oleo, 2021)
This research is motivated by strategic issues that develop in society which shows that the performance of the state civil apparatus in fostering street children in Kendari City is still considered lacking, seen from street children who still roam the streets of Kendari City and there are still some obstacles in the implementation of child development. the streets. Therefore, this research aims toknowing and describing the performance of the state civil apparatus in fostering street children at the Kendari City Social Service.The research method used is a qualitative research method with a descriptive approach. The informants in this study were the State Civil Apparatus of the Kendari City Social Service and street children who had been caught by the Kendari City Social Service. Data collection techniques were carried out by means of observations, interviews, and documentation. Then the data analysis technique used in this study was carried out by means of data collection, data reduction, data presentation and drawing conclusions. The results showed that the performance of the State Civil Apparatus of the Kendari City Social Service in handling street children that had been carried out so far had not been maximized, there were no handling efforts related to the development of street children carried out by the Social Service because of several obstacles including limited funds and human resources, public participation and awareness as well as awareness of street children themselves are still lacking, as well as a special coaching center to accommodate street children such as a halfway house that does not yet exist in the Kendari City Social Service.